Benign Paroxysmal Vertigo of Childhood - Pawar, Vishal Gurunath (Annals of Otology and Neurotology, 2018)
The aim of the article is to describe a case of benign paroxysmal vertigo (BPV) in childhood. It emphasizes the fact that every dizziness is not vertigo and every vertigo is not benign paroxysmal positional vertigo. BPV in childhood often goes unrecognized. This case report aims at creating awareness about this benign and self-limiting disorder.
Keywords: paroxysmal vertigo of childhood; BPV of childhood; migraine variant